The Impact of Fintech Accounting on MSME Reporting in Denpasar City - Ni Made Adelia Purnama; A.A. Ayu Erna Trisnadewi; I Wayan Gde Yogiswara Darma Putra (PT Keberlanjutan Strategis Indonesia, 2026)
The development of MSMEs in Denpasar City is so fast and competitive, which is driven by the high frequency of transactions from domestic and foreign tourists. Despite the massive and significant number, most of the MSME actors in Denpasar City still face fundamental obstacles in financial management and accounting reporting. This suboptimal reporting condition creates serious consequences because it directly hinders MSME access. This study aims to determine the influence of the use of fintech accounting on MSME reporting. The location of this research is in MSMEs in Denpasar City. The population in the study is MSMEs located in the Denpasar City area, have used Fintech Accounting (digital recording application) in their operational activities and are engaged in the coffee shop sector which has been running its business for at least 1 year and a research sample of 100 respondents. The data analysis method used is simple regression analysis. The results of this study show that the use of fintech accounting has a positive and significant effect on MSME reporting.